2021
DOI: 10.3390/ijms222413279
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Co-Expression Analysis Network-Based Analysis on the Candidate Pathways and Hub Genes in Eggplant Bacterial Wilt-Resistance: A Plant Research Study

Abstract: Solanum melongena L. (eggplant) bacterial wilt is a severe soil borne disease. Here, this study aimed to explore the regulation mechanism of eggplant bacterial wilt-resistance by transcriptomics with weighted gene co-expression analysis network (WGCNA). The different expression genes (DEGs) of roots and stems were divided into 21 modules. The module of interest (root: indianred4, stem: coral3) with the highest correlation with the target traits was selected to elucidate resistance genes and pathways. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…WGCNA OF A. MUELLERI RESISTANCE TO SOFT ROT RESISTANCE. WGCNA uncovers key genes or metabolic pathways by aggregating highly related gene groups in the transcriptome and associating them with sample characteristics (Langfelder and Horvath 2008;Peng et al 2021;Wang et al 2022). The five target modules of interest selected in our study were expressed significantly after inoculation with Pcc KEGG pathways enriched in a-linolenic acid metabolism, phenylpropane biosynthesis, plant hormone signal transduction, and plant-pathogen interaction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA OF A. MUELLERI RESISTANCE TO SOFT ROT RESISTANCE. WGCNA uncovers key genes or metabolic pathways by aggregating highly related gene groups in the transcriptome and associating them with sample characteristics (Langfelder and Horvath 2008;Peng et al 2021;Wang et al 2022). The five target modules of interest selected in our study were expressed significantly after inoculation with Pcc KEGG pathways enriched in a-linolenic acid metabolism, phenylpropane biosynthesis, plant hormone signal transduction, and plant-pathogen interaction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA is an efficient method to reveal the correlation between gene modules and phenotypic traits [ 11 , 12 ]. In this study, only two gene modules (MEpurple and MEdarkturquoise) significantly associated with S. scitamineum infection ( p < 0.01) were identified from WGCNA ( Figure 3 , Table 2 ), while other modules were not.…”
Section: Discussionmentioning
confidence: 99%
“…Weighted gene co-expression network analysis (WGCNA) is an efficient method for mining modules and hub genes related to traits of interest [ 10 ] and has been successfully used to construct gene co-expression networks in different species [ 11 , 12 , 13 ]. In this report, a WGCNA approach was used to identify modules and hub genes associated with S. scitamineum infection.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq results showed that eggplant resistance to bacterial wilt involved in cell death pathways, cell receptor signaling pathways ( Chen et al, 2018 ). Peng et al (2021) showed that the MAPK signaling pathway, plant pathogen interaction, and glutathione metabolism were co-enriched in roots and stems after inoculation with R. solanacearum . Further research showed that SmRPP13L4 positively regulated the resistance of eggplant to bacterial wilt ( Peng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%